Gerakan Pencegahan Stunting Melalui Sosialiasi Bersama Pemuda IPNU DAN IPPNU Desa Tengki Kecamatan Brebes Kabupaten Brebes - Siti Warkhatun Solihah; Ahmad Krisdiyanto; Lia Kholifah Dwi Rahayu Lestari; M.Zidny Nafi' Hasbi (Bangun Desa: Jurnal Pengabdian Masyarakat, 2024)
Abstract Stunting is a condition where growth failure in children occurs due to chronic malnutrition over a long period of time, thus hampering growth and development. In this research we used an observation method where we went directly into the field with health workers to see what conditions were in the community of Tengki Village, Brebes. . The population and sample in this research were all Tengki residents. Efforts to prevent stunting that can be made are by providing adequate nutritional intake from the fertilization of the egg until the child is 2 years old,providing exclusive breast milk until the baby is 6 months old, and ensuring that the child receives complete immunization. The conclusion of this research is the prevention of stunting in the Tengki Village area, Kab. Brebes can be done through the observation and socialization stages. This activity started with observations carried out by all members of KKNT group 6 of Tengki Village, Brebes Regency, counseling activities regarding stunting prevention were attended by 50% of Tengki Village teenagers and education on the provision of additional food was provided by 80% of the Tengki Village community.Key words: stunting, KKN-T, prevention.